Assessing Student Attendance and Question Selection in a Circuit Theory Course - Enochoghene, Samuel Oghenenyerovwo; Ayanlade, Samson Oladayo; Olayiwola, Olufemi Isaac (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
This study investigated the relationship between class attendance and the choice of exam questions in a circuit theory course within an electrical engineering program at a Nigerian university. The course comprised four modules: Foster & Cauer LC Network Realisation, Two Port Network Synthesis, Filter Fundamentals, and State Variable Method to Circuit Analysis. Thirteen students, who attended at least one class and took the final exam, participated in the study. Data was collected on attendance and exam performance, focusing on which questions were chosen by the students and their attendance rates. Analysis revealed that while attendance was generally low, with an average of 35%, it had some influence on the choice of exam questions. The highest attendance rate was 84%, and the lowest was 5%. Most students opted for questions on Foster & Cauer Form and Two Port Network Analysis, with question five being the most attempted. This suggests a potential correlation between topics covered in class and their selection in exams, indicating the importance of in-person engagement for understanding complex concepts. The study concludes that while class attendance did impact question choice, other factors such as student motivation and participation likely play significant roles.